SHEEP BRUCELLOSIS IN GADARIF STATE,SUDAN - Mohamed,; I. M,; Ahmed Nour, Adam; G.O,; Abdalla,; M.A,; Siham,; Ahmed Nour, E.S; Khalid,; Ahmed G, M. (Journal of Veterinary Medicine and Animal Production, 2022)
A total of 250 serum samples were collected from sheep in Alglabat area, Gadarif State using venipuncture of jugular vein. The samples were examined for the presence of brucella antibodies using Rose Bengal Plate Test (RBPT) and ELISA. All samples were negative for brucellosis.